Turnover: A generator of technical efficiency in Agro-industrial SMEs in Cameroon - AZEBAZE KENFACK , Fabrice Parfait; TAKOUDJOU NIMPA , Alain (Revue Internationale des Sciences de Gestion, 2024)
Staff turnover has been the subject of several mixed debates in the world, in Africa and in Cameroon. This study aims to evaluate the degree of technical efficiency of agro-industrial SMEs (Small and Medium-sized Enterprises) in Cameroon while showing the effects of staff turnover on their degree of efficiency. To realize this study, data from 103 SMEs in the agro-industrial sector in Cameroon were gotten from the National Institute of Statistics (NIS) of Cameroon from 2018 to 2022. The DEA (Data Employment Analysis) method was used to measure the efficiency and the Tobit regression used for analysis with both DEA technology models, the Constant Scale Return model and the Variable Scale Return model. The results show firstly that, SMEs in the agro-industry sector in Cameroon have a low level of technical efficiency. Secondly, the technical efficiency of these SMEs is significantly and positively influenced by turnover as such, a low level of turnover improves the technical efficiency of agro-industrial SMEs in Cameroon. To improve their technical efficiency, SMEs are recommended to keep a low turnover.